Perioperative nursing management for patients undergoing HoLEP with MOSES technology (MOSES-HoLEP术围手术期的护理) - MENG Jin (孟瑾); WANG Min (王敏); ZHU Feng (祝枫) (中西医结合护理)
This paper summarized the clinical data and perioperative nursing management for 40 patients undergoing HoLEP with MOSES technology. Perioperative nursing interventions included preoperative preparation and health education, postoperative bladder irrigation, placement and maintenance of indwelling catheter, PCA infusion pump management, pain evaluation, prevention on venous thromboembolism, and care for urinary incontinence after surgery. (本文总结40例实施经尿道前列腺钬激光剜除术(HoLEP)术患者的围手术期护理体会, 主要包括术前准备及健康教育, 术后持续膀胱冲洗, 留置导尿管的护理, PCA泵规范使用的护理及疼痛评估, 静脉血栓栓塞症的预防措施, 以及术后尿失禁的干预措施等。)